Structural, optical and luminescence studies of CuO doped MgZn2(PO4)2 nanopowder variants for solid state optical devices - Gidla Rabecca Rani; Srinivasarao Kuna; Daniel Kodamala; Shaik Azad Basha; Sandhya Cole (Next Materials)
Solid-state reaction method was used to prepare Copper Oxide (CuO) doped Magnesium Zinc Phosphate (MgZn2(PO4)2 = MZP) nanopowders. P-XRD), FE-SEM with EDS, FT-IR, DRS and PL studies have been used to analyze the prepared samples. Their monoclinic structure, with a P21/n space group which is well matched with JCPDS Card No: 00–031–1468 and crystallite sizes around 30–50 nm by using Scherer's and W-H approach, was examined by XRD scrutiny. Zn, Mg, P, O, and Cu were verified by EDS, and FE-SEM revealed a shape resembling clustered foam. Phosphate ion vibrational bands were identified using FT-IR analysis. A straight bandgap of 3.00–3.16 eV was found in DRS investigations. The prepared samples show an emission at 381 nm upon excitation at 447 nm, according to the PL spectrum. The colour-correlated temperature, color purity, and color rendering index were also determined. The produced samples showed promising for applications in solid-state optical lighting systems.